If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2q + -1) = 2q + 8q Reorder the terms: 6(-1 + 2q) = 2q + 8q (-1 * 6 + 2q * 6) = 2q + 8q (-6 + 12q) = 2q + 8q Combine like terms: 2q + 8q = 10q -6 + 12q = 10q Solving -6 + 12q = 10q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-10q' to each side of the equation. -6 + 12q + -10q = 10q + -10q Combine like terms: 12q + -10q = 2q -6 + 2q = 10q + -10q Combine like terms: 10q + -10q = 0 -6 + 2q = 0 Add '6' to each side of the equation. -6 + 6 + 2q = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 2q = 0 + 6 2q = 0 + 6 Combine like terms: 0 + 6 = 6 2q = 6 Divide each side by '2'. q = 3 Simplifying q = 3
| N+3.4=5.6 | | n/5+3-10=30 | | a(bx-2)=cx+6 | | 6(4.5y)-12=9 | | (a+9)(a+2)=0 | | p+0.06p=148.4 | | n*5+3-10=30 | | 5x-5=4x+7 | | 15-2x-2=10x+3x+2 | | 4-5x=2(7x-3) | | -8-5n=4m | | 2(-1)+5+3x-3=5x+9 | | 8=-5+x | | 2r+4=2r-5 | | 10D+40=10 | | 25=7+3k-17 | | 13-4x+2=3x-7x+2 | | 2p+3p= | | 1+(-40+5x)=2+-1(x+5) | | 8=-5+8 | | -4.4-1.21z= | | 5x-12+15x-7+9-2x=-15 | | 12-7x-10=x-8x+2 | | t^2-2=0 | | 3a+4(2a-17)=-13 | | 9.99x+.25=113.74 | | 32x-21+-5x+30= | | 1=6p+6-p | | -(3x+2)-(x-1)=(2x-2)-(2x+4) | | 10-3x-1=7+3x+2 | | 1+5(x-8)=2-1(x+5) | | -2=v-6 |